Towards an Integrative-Critical Islamic Epistemology: A Comparative Analysis of al-Faruqi and Sardar - Khabib Solihin; Umi Latifah (Journal of Islamic Studies and Civilization, 2025)
This study is motivated by the epistemological crisis in Islamic scholarship, driven by the dominance of secular Western paradigms and the dichotomy between religious and secular sciences. It aims to analyze and compare the epistemological frameworks proposed by Ismail Raji al-Faruqi and Ziauddin Sardar in addressing these issues. This research employs a qualitative method with a comparative approach through a literature review of scholarly works examining the thoughts of both figures. The findings indicate that al-Faruqi proposes the Islamization of knowledge as an integrative approach, reconstructing modern sciences within a tawhidic framework. In contrast, Sardar advances the concept of the “Islamization of knowledge” in a more transformative sense, emphasizing the construction of knowledge grounded fundamentally in the Islamic worldview. Discursively, al-Faruqi demonstrates strength in operational and practical dimensions, whereas Sardar offers greater depth in philosophical inquiry and epistemological critique. This study concludes that an integrative-critical synthesis of these two perspectives is essential for developing an authentic, contextual, and relevant Islamic epistemology capable of addressing contemporary intellectual challenges.